Recent advance in the pathology of pitutiary adenomas (2015)
Introduction: Pituitary adenomas are the third most common intracranial tumours. The 2004 WHO classification of pituitary adenomas has recommended the use of immunohistochemistry, electron microscopy and molecular techniques along with clinical and morphological evaluation in making a diagnosis. This review examines the subtypes of pituitary adenomas seen using the different diagnostic techniques. Materials and Methods: A comprehensive search of literature as well as an online search of databases was made. Results: The classification and molecular properties of the different subclasses are highlighted in this review. Pituitary adenomas are among the most frequent intracranial tumours and can present with over-expression of the hormones normally produced by the pituitary gland or pressure symptoms from the tumour. Pituitary adenomas are clonal tumours and often show over-expression of tumour suppressor genes which can sometimes be familial. Molecular studies have shown expression of common genes that can be employed to group pituitary adenomas based on their histogenetic origin. These genetic properties can be helpful in delineating those tumours which do not show clear cut lineage. This is particularly useful in the assessment of silent and plurihormonal adenomas. Several subclasses exist and the presentation may be different depending on the particular hormone produced. The prolactinomas are the commonest type followed by the silent adenomas with Gonadotroph and TSH producing adenomas constituting the rare types. Conclusion. Pituitary carcinomas are rare tumours diagnosed only in the presence of metastatic deposits in other tissues.